TROVA outputs for the extratropical transition of tropical cyclones in the North Atlantic basin - Albenis Pérez-Alarcón; Patricia Coll-Hidalgo; José C. Fernández-Alvarez; Ricardo M. Trigo; Raquel Nieto; Luis Gimeno (Zenodo, 2023)
Output data from theTRansport Of water Vapor (TROVA) tool for the research paper "Evaluating changes in the moisture sources for tropical cyclones precipitation in the North Atlantic that underwent extratropical transition".